2018
DOI: 10.2147/amep.s160997
|View full text |Cite
|
Sign up to set email alerts
|

Review of mini-clinical evaluation exercise (mini-CEX) in a psychiatry clerkship

Abstract: BackgroundDirect observation of medical students with actual patients is important for the assessment of clinical skills including interviewing and counseling skills. This article describes medical students’ experience of mini-clinical evaluation exercise (mini-CEX) during their clerkship in consultation psychiatry.Materials and methodsIn our center during inpatient consultation psychiatry clerkship, all rotating students are expected to complete one mini-CEX assessment as part of their clinical training. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…In our pilot study, the highest mean Mini‐CEX scores for these orthodontic residents were in the organization/efficiency domain, indicating that they were able to prioritize their findings and construct a differential diagnosis and treatment plan in a systematic manner. However, studies with medical trainees found that professionalism was the domain with the highest mean scores 17, 18 . These differences could be attributed to the difference between medical and dental education methodologies, settings, and procedures evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our pilot study, the highest mean Mini‐CEX scores for these orthodontic residents were in the organization/efficiency domain, indicating that they were able to prioritize their findings and construct a differential diagnosis and treatment plan in a systematic manner. However, studies with medical trainees found that professionalism was the domain with the highest mean scores 17, 18 . These differences could be attributed to the difference between medical and dental education methodologies, settings, and procedures evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies with medical trainees found that professionalism was the domain with the highest mean scores. 17,18 These diferences could be attributed to the diference between medical and dental education methodologies, settings, and procedures evaluated. The lowest mean scores in our study were in the clinical judgment domain.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 15 ] It can be, therefore, implied that mini-CEX as a tool has good acceptability and feasibility, as suggested by the feedback responses, and this substantiates the findings of earlier studies. [ 6 7 8 10 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…To best of our efforts, we could identify only three studies in this regard. [ 6 7 8 ] Hence, we planned to take up this study.…”
Section: Introductionmentioning
confidence: 99%
“…The emphasis on counselling included student's interaction with the patient professionally (introduced himself/herself, maintained good eye contact) and education (explained the rationale for test/treatment). After the interview, the examiner (attending) completed the rating form and provided feedback [54]. Psychological aspects of medical care give an additional opportunity for hospital psychiatry, and the internship offers interpersonal experiences of the clinical encounter and medical care [55].…”
Section: Introductionmentioning
confidence: 99%